Pengaruh pemberian vitamin C dan Vitamin E terhadap tantangan E. Coli Patogen pada ayam Pedaging - I Wayan Batan; Bibiana W. Lay; Aisjiah Girinda; Hernomoadi Hoeminto (Hemera Zoa, 1993)
This study was undertaken to asses the effects of dietary vitamin C, vitamin E, vitamin C and vitamin E, combined with E. coli bacterin against patogenic E. coli challenge in broiler chickens.The completely randomized design was used, in 4 x 2 factorialexperiment i.e. consisted 4 vitamins and two bacterins. Each treatment combination had 10 chicks as replication, hence 80 broiler chicks were used in this study. Data obtained from the study were analysed using analysis of variance or Kruskal Wallis test in order to identify the influence of treatment factor and their interactions.The chickens were fed standard ration supplemented with 300 mg vitamin E or 330 mg vitamin C or 300 mg vitamin E and 330 mg vitamin C or no vitamin supplement per kg ration as control.E. coli bacterin inactivated by heat, was given to the chickens when they were 2 weeks old. The bacterin was injected directly to the airsacs of the treatment groups.At 4 weeks of age, all of the chickens were challenged with patogenic E. coli given directly to the airsacs.The data showed that the supplemental of either vitamin E, vitamin C, or vitamin E and vitamin C significantly reduced pathological lesions caused by E. coli challenge, whilst the E. colli bacterin alone did not. Suplemental vitamin C, or vitamin C and vitamin E, and also injection of E. coli bacterin significantly reduced chicken body weight.